Sharia Economic Dispute Settlement Between Religious Courts And Basyarnas - Oslami, Achmad Fikri (Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to examine the settlement of sharia economic disputes that arise in the event of a dispute between the two parties. This study will answer the formulation of the problem, namely: Why can the settlement of sharia economic disputes be resolved through the Basyarnas and the Religious Courts? the impact of resolving sharia economic disputes through Basyarnas and the Religious Courts; Basyarnas status after the enactment of Law Number 50 of 2009 concerning the Second Amendment to Law Number 7 of 1989. In this study, the authors used literature research, then analyzed it using content analysis methods related to the problems studied. The research method used is a normative juridical research method. The results of this study state that the birth of Law Number 03 of 2006 which has been updated with Law Number 50 of 2009 has brought major changes to the existence of the current Religious Courts, one of the fundamental changes is that the Religious Courts have the authority to examine, hear, and resolve sharia economic disputes through litigation. The settlement of sharia economic disputes as regulated in Law Number 30 of 1999 has been carried out by Basyarnas and is still used as a non-litigation institution authorized to resolve disputes.